The effects of high intensity neuromuscular electrical stimulation on abdominal strength and endurance, core strength, abdominal girth, and perceived body shape and satisfaction - Porcari, J.; Ryskey, A.; Foster, C. (International Journal of Kinesiology & Sports Science, 2018)
Background: Neuromuscular electrical stimulation (NMES) has been used clinically for many years as a modality to improve muscular strength and endurance. Recently, equipment manufacturers have developed over-the-counter NMES units to target specific muscle groups, particularly the abdominal region. Objective: To study the effects of self-administered neuromuscular electrical stimulation (NMES) on changes in abdominal muscle strength and endurance, core strength, abdominal girth, and subjective measures of body satisfaction and shape. Methods: Fifty-three adults were randomly assigned into high intensity (HI: n=27) or low intensity (LI: n=26) groups. The NMES device for the LI group had been altered so that subjects felt some tactile sensation, but the intensity was not sufficient to elicit a muscular contraction. All subjects stimulated their abdominal muscles 5 days per week (30 minutes per session) for 6 weeks. Subjects were tested at Baseline, 2, 4, and 6 weeks. Results: The HI group had a significantly greater increase in strength at 4 weeks (19%) and 6 weeks (29%) compared to the LI group and performed significantly more curl-ups than the LI group at 2 weeks (62%). Both groups had a significant increase in core strength over the course of the study, with no difference between groups. There was no change in abdominal girth between groups. Both groups had significant improvements in body satisfaction from Baseline to 4 weeks and Baseline to 6 weeks, with no significant interaction. Conclusions: Results of the current study indicate that high intensity NMES can significantly increase abdominal strength and endurance compared to LI intensity (control) stimulation. Results for subjective measures tended to favor the HI group, but were less conclusive, since the LI group also had some positive changes.